PENGARUH PENERAPAN LKS BERORIENTASI MODEL PEMBELAJARAN REFLEKSI TERHADAP PENCAPAIAN KOMPETENSI FISIKA SISWA KELAS X DI SMAN 5 PADANG - Rahmad Efendi; Masril Masril; Ratnawulan Ratnawulan (PILLAR OF PHYSICS EDUCATION, 2015)
Competency of students in physics class X cross-interest in SMAN 5 Padang has not achieved well. This is due to lack of interest or motivation of students in studying physics, and worksheets that use less attractive and makes learning becomes meaningful. This study carried out to investigate the effect of the applicatio-  LKS oriented reflection learning model on the achievement of competence physics class X in SMAN 5 Padang. The type of this research is a quasi-experimental with Randomized Control Group Only Design. The Populations of this research were all students in class X IS in  SMAN 5 Padang is who listed in the academic year 2014/2015. Sample of this research was selected by purposive random sampling technique and the class was selected as the experimental class is X IS 3 and the control class is X IS 4. The instrument is used to collect data is written test for cognitive competency and observation sheet for affective competence and performance assessment form for the psychomotor competency. Based of the research that has been done, it was concluded that the LKS oriented reflection learning model can improve the competency of physics students in competency knowledge and skills but not the attitude of competency